Using a trait‐based approach to measure the impact of dam closure in fish communities of a Neotropical River. Issue 1 (5th April 2017) - Lima, Ana C.; Sayanda, Diogo; Agostinho, Carlos S.; Machado, Ana L.; Soares, Amadeu M.V.M.; Monaghan, Kieran A.
Abstract: Damming is one of the main causes of the global decline in freshwater biodiversity. Yet, many hydroelectric dams are being built (or planned) in the Neotropics, where the high species diversity and lack of basic ecological knowledge provide a major obstacle to understanding the effects of this environmental change, which has been mostly described from the perspective of taxonomic change. However, this approach does not account for biological function. Trait‐based analysis provides an alternative approach to bioassessment. We assessed the impact of dam closure on the functional structure of fish communities of a Neotropical river by applying trait‐based analyses to the response of individual traits aggregated at the assemblage level. Fish data were collected during three distinct time periods (1 year before, 1 year after and 5 years after dam closure), at eight sites located downstream of the dam, in the reservoir, transition zone and upstream. The results indicated that reproduction strategies (migration and parental care) and diet (detritivores) were the trait categories mostly affected by the dam, with the response of downstream assemblages differing from upstream of the dam. A trait‐based analysis to the impact of damming on fish communities appears to be a promising approach using an initial descriptive analysis of individual traits and regression models of multiple traits that reflect species' adaptation to the new environment. This study provides both an alternative and complementary approach to taxonomic assessment of impacts from damming, contributing towards a more robust evaluation of the response of fish communities to dams.